Identifying and Understanding the Language Curriculum Across the World - Christine N. Ferrer; Aubrey S. Somera (IJOTL-TL (Indonesian Journal of Language Teaching and Linguistics))
This article compares and contrasts the Language Curriculum in the United States, United Arab Emirates, Mongolia, Philippines and Indian Language Curriculum for the year 2022. This is a comparative analysis; a research journal conducted to analyze the ideological, cultural, and political-economic elements that impact the development of language curricula in five different countries. Furthermore, the educational goals and ideologies that underpin both curricula are discussed. A very intriguing conclusion emerges when considering the curricula's unspoken aims. All the five (5) nations' language and literature curricula emphasize the significance of citizenship and character education and are interwoven into curricula instruction.